Raw Materials Synthesis from Heavy Metal Industry Effluents with Bioremediation and Phytomining: A Biomimetic Resource Management Approach - Salmah B. Karman; S. Zaleha M. Diah; Ille C. Gebeshuber (Advances in Materials Science and Engineering)
Heavy metal wastewater poses a threat to human life and causes significant environmental problems. Bioremediation provides a sustainable waste management technique that uses organisms to remove heavy metals from contaminated water through a variety of different processes. Biosorption involves the use of biomass, such as plant extracts and microorganisms (bacteria, fungi, algae, yeast), and represents a low-cost and environmentally friendly method of bioremediation and resource management. Biosorption-based biosynthesis is proposed as a means of removing heavy metals from wastewaters and soils as it aids the development of heavy metal nanoparticles that may have an application within the technology industry. Phytomining provides a further green method of managing the metal content of wastewater. These approaches represent a viable means of removing toxic chemicals from the effluent produced during the process of manufacturing, and the bioremediation process, furthermore, has the potential to save metal resources from depletion. Biomimetic resource management comprises bioremediation, biosorption, biosynthesis, phytomining, and further methods that provide innovative ways of interpreting waste and pollutants as raw materials for research and industry, inspired by materials, structures, and processes in living nature.